(3aGFOI aj CQHYjf MOjKkGs - (3Ydj Hf aJM Gddg GdcGTGfj, GdQVGs
(3ChdgG (B:s
(3ef GdCQHYjf MOjKkG GdPi LeYgG Gdehdi GdaGVd GdcGTGfi QMeg Gddg Qhi GdTQja GdRGgO bGd cfG YfO GdhRjQ Yhf GdOjf jMji Hf gHjQI ai TgQ QeVGf HGdSfI GdebOe PcQgG hfMf Ydi WHbI hYfOg LeGYI s
(3BNQgG (B:s
(3bGd JPcQ TgQ QeVGf ajbhd fYe ajbhd SJQ GdMGd TQW agPG HeG SeYJg hQhjJg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs